The changing of world business megatrends and Thailand in the future - Tophothai, Narut (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
Nowadays, we can not deny that the economy is a major force in running the well-being of everyone in the world, not only the global economy, but also the economy in each country. The global economy give the directly impact on the economies of every countries such as Thailand. The strongly economy in each country give effect to the living conditions of the people. The production of goods and service have to concern on demand and popularity of the public needs. In each social has different needs and demand of the target. Furthermore, civilize social has more advance in new demands and needs, because needs is something that is always happen to the saturation point. Thus, analysts economic data must be analyze and provide the clearly business detail and information to benefit the public and private sectors in the business. Therefore, it become very important to survey and analyze data on customer needs now and in the future. The result give the data of needs of everyone that can be improve and innovate to meet the need of everyone. These can give a direct benefit to businesses to develop and initiate key business trends of the business that are emerging in the future. Article history : Accepted 27 October 2015 SIMILARITY INDEX = 0.00